2003
DOI: 10.1086/368012
|View full text |Cite
|
Sign up to set email alerts
|

The Largest Black Holes and the Most Luminous Galaxies

Abstract: The empirical relationship between the broad-line region size and the source luminosity in active galactic nuclei (AGNs) is used to obtain black hole (BH) masses for a large number of quasars in three samples. The largest black hole masses exceed and are found to occur in the objects with the highest luminosities. 1010 M , Such BH masses, when converted to galaxy bulge mass and luminosity, indicate masses in excess of 13 10 M , and in excess of 700 km s Ϫ1 . Such massive galaxies have never been observed. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
126
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(141 citation statements)
references
References 25 publications
13
126
2
Order By: Relevance
“…The use of a single source (actually, two single sources) is what sets this study apart from past investigations, particularly on the point of understanding the effect of variability on SE masses. This is an important distinction, given that Kelly & Bechtold (2007) show that an intrinsic correlation between M BH and L that is statistically independent of the R-L relationship (supported by, e.g., Corbett et al 2003;Netzer 2003;Peterson et al 2004) can lead to an artificially broadened SE mass distribution when it is composed of masses from multiple sources. They suggest that because of this intrinsic M BH -L relation, using the luminosity simply as a proxy for the BLR radius may cause additional scatter in the mass estimates because additional information about the BH mass that may be contained in L is ignored.…”
Section: Signal-to-noise Ratio (S/n)mentioning
confidence: 96%
“…The use of a single source (actually, two single sources) is what sets this study apart from past investigations, particularly on the point of understanding the effect of variability on SE masses. This is an important distinction, given that Kelly & Bechtold (2007) show that an intrinsic correlation between M BH and L that is statistically independent of the R-L relationship (supported by, e.g., Corbett et al 2003;Netzer 2003;Peterson et al 2004) can lead to an artificially broadened SE mass distribution when it is composed of masses from multiple sources. They suggest that because of this intrinsic M BH -L relation, using the luminosity simply as a proxy for the BLR radius may cause additional scatter in the mass estimates because additional information about the BH mass that may be contained in L is ignored.…”
Section: Signal-to-noise Ratio (S/n)mentioning
confidence: 96%
“…The availability of the new rest-frame UV black-hole mass estimators has been exploited by recent studies to investigate the black-hole masses of the most luminous quasars (Netzer 2003), the evolution of the black-hole mass -luminosity relation (Corbett et al 2003) and also to estimate the mass of the most distant known quasar at z = 6.41 (Willott, McLure & Jarvis 2003;Barth et al 2003). In particular, using composite spectra generated from ≥ 22000 2dF+6dF quasars, Corbett et al (2003) successfully demonstrated that the evolution of the black-hole mass -luminosity relation is too weak to explain the evolution of the z ≤ 2.5 quasar luminosity function with a single population of long-lived objects.…”
Section: Introductionmentioning
confidence: 99%
“…This new information is then used to address important questions regarding the virial black-hole mass estimator and the the accretion rate of luminous quasars. Firstly, a recent study by Netzer (2003) based on the Civ and Hβ virial mass estimators has suggested that many luminous quasars at z > ∼ 2 may harbour central black holes with masses in excess of 10 10 M⊙. As highlighted by Netzer (2003), since galaxies with suitably large velocity dispersions (σ > ∼ 600 km s −1 ) are not observed at low redshift, this result raises questions about either the reliability of the virial mass estimator, or the form of the bulge:black-hole mass relation, at high redshift.…”
Section: Introductionmentioning
confidence: 99%
“…This gives a BH mass about 60% of the one obtained using a fixed α (=−0.3), in the worst case. Depending on the exact slope in this α × log L V relation, it could at least partially help to explain the discrepancy between the observations and the predictions of host galaxy bulges as large as 10 13 M (Netzer 2003). This demands more data analysis to evaluate, for instance, how far back in time (i.e.…”
Section: Samples Analysis and Discussionmentioning
confidence: 99%
“…In Netzer (2003), Bj photometric luminosities are used in BH mass estimates, when analyzing a sample of 1000 LBQS quasars. The author argues that the assumption of a power-law L ν ∝ ν α with a single α (=−0.5) for the whole population can affect the mass estimates.…”
Section: Introductionmentioning
confidence: 99%